2023
DOI: 10.3389/fcimb.2023.1142029
|View full text |Cite
|
Sign up to set email alerts
|

Progress of polymer-based strategies in fungal disease management: Designed for different roles

Abstract: Fungal diseases have posed a great challenge to global health, but have fewer solutions compared to bacterial and viral infections. Development and application of new treatment modalities for fungi are limited by their inherent essential properties as eukaryotes. The microorganism identification and drug sensitivity analyze are limited by their proliferation rates. Moreover, there are currently no vaccines for prevention. Polymer science and related interdisciplinary technologies have revolutionized the field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 275 publications
(351 reference statements)
0
1
0
Order By: Relevance
“…To circumvent the aforementioned issues with antifungal peptides, controlled polymerization techniques have been used to prepare synthetic macromolecules that mimic the overall properties of antifungal peptides. As controlled polymerization techniques are highly tolerant to different functional groups, they are especially well suited to mimic antifungal peptides, which contain a mixture of various charged and uncharged amino acids with defined chain lengths. , Zhang and co-workers showed that the combination of a positively charged ammonium group and hydrophobic groups in a synthetic polymer increased antifungal activity compared to the respective homopolymers . Additional work has demonstrated that the incorporation of an uncharged functional group, such as hydroxyl groups, into amphiphilic polymers decreased the hemolytic activity and protein aggregation, in turn increasing bioavailability in antibacterial studies. , Recently, our group studied the influence of the hydrophobicity and molecular weight of ternary, amphiphilic polyacrylamides on their antifungal activity and biocompatibility .…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent the aforementioned issues with antifungal peptides, controlled polymerization techniques have been used to prepare synthetic macromolecules that mimic the overall properties of antifungal peptides. As controlled polymerization techniques are highly tolerant to different functional groups, they are especially well suited to mimic antifungal peptides, which contain a mixture of various charged and uncharged amino acids with defined chain lengths. , Zhang and co-workers showed that the combination of a positively charged ammonium group and hydrophobic groups in a synthetic polymer increased antifungal activity compared to the respective homopolymers . Additional work has demonstrated that the incorporation of an uncharged functional group, such as hydroxyl groups, into amphiphilic polymers decreased the hemolytic activity and protein aggregation, in turn increasing bioavailability in antibacterial studies. , Recently, our group studied the influence of the hydrophobicity and molecular weight of ternary, amphiphilic polyacrylamides on their antifungal activity and biocompatibility .…”
Section: Introductionmentioning
confidence: 99%